Pola dan perilaku konsumsi daging ayam ras rumah tangga peserta Program Keluarga Harapan Kota Pekanbaru, Provinsi Riau: Patterns and behavior of broiler chicken meat consumption in households participating in the Program Keluarga Harapan in Pekanbaru City, Riau Province - Oktavia, Vilandra; Bakce, Djaimi; Yusri, Jumatri (Analisis Kebijakan Pertanian, 2025)
The background of this research was that per capita consumption of broiler chicken meat was lower than the recommended nutritional adequacy in households receiving the Family Hope Program (Program Keluarga Harapan/PKH) in Pekanbaru City, Riau Province. The objective of this study was to analyze broiler chicken meat consumption patterns and identify the factors that influence them among PKH households. Respondents in this study were 315 PKH households, selected through a multistage sampling approach using simple random sampling techniques. Data were analyzed using descriptive statistics and multiple linear regression. The findings show that broiler chicken meat consumption was significantly affected by broiler chicken meat price, other poultry product prices, beef prices, cooking oil prices, household size, household income, and the occupation of the household head, with a significance level of 5%. The per capita/day consumption pattern of broiler chicken meat differs by demographic characteristics, averaging 20.36 grams, far below the Ministry of Health’s recommendation of 80 grams, reflecting limited purchasing power and nutritional awareness among low-income households. The policy implication of this research is that the government should implement policies to stabilize food prices, promote community economic empowerment, and provide nutritional education to increase consumption of broiler chicken meat as a source of protein among households of PKH participants and ensure it aligns with recommended dietary standards.
Keywords: konsumsi; daging ayam ras; rumah tangga; program keluarga harapan; broiler meat; consumption; households; Program Keluarga Harapan